Antiphospholipid syndrome: Diagnosis and management in the obstetric patient. (April 2020) - Arslan, Erol; Branch, D. Ware
Abstract: Antiphospholipid syndrome (APS) is a rare condition clinically characterized by thrombotic events or pregnancy complications and confirmed by one or more repeatedly positive antiphospholipid antibodies on two or more occasions at least 12 weeks apart. Several factors are thought to have roles in the pathogenesis of adverse obstetric events related to APS, including platelet and endothelial cell activation, complement activation, and ultimate activation of the thrombotic pathway. Despite standard treatment with a heparin agent and low-dose aspirin, 30% of women with definite APS cannot achieve a successful pregnancy outcome. Additional treatment options are still controversial, and prospective trials with appropriate controls are needed to investigate the efficiency of alternative treatments. In this chapter, we discuss diagnostic, clinical, and therapeutic approaches in the treatment of APS syndrome in pregnancy. Highlights: Pregnancies in patients with APS are at risk for adverse outcomes and require a multidisciplinary approach including MFM, hematology, and rheumatology The accepted standard treatment regimen of APS during pregnancy is a heparin agent plus low-dose aspirin (LDA). Patients with a history of a thrombotic event who are on warfarin should be switched to a heparin agent before 6 th  week of gestation to avoid embryopathy Women with lupus anticoagulant are at increased risk for adverse pregnancy outcomes in spite of treatment with a heparin agent and LDA.